Expert Consensus on the Clinical Application of PI3K/AKT/mTOR Inhibitors in the Treatment of Breast Cancer (2025 Edition) - The Breast Cancer Expert Committee of the National Quality Control Center for Cancer; The Expert Committee on Cancer Prevention and Treatment of the Health China Research Center; The Society of Clinical Research on Oncology Medications of the China Anti‐Cancer Association; The Society of Onco‐Pathology of the China Anti‐Cancer Association (Cancer Innovation)
ABSTRACT Background The phosphoinositide 3‐kinase (PI3K)/protein kinase B (PKB or AKT)/mammalian target of rapamycin (mTOR) signaling pathway (PAM pathway) plays a critical role in breast cancer pathogenesis and progression, and is closely linked with resistance to endocrine therapy in advanced breast cancer. Randomized clinical trials have shown that PI3K/AKT/mTOR inhibitors deliver significant clinical benefits, particularly for patients with advanced hormone receptor (HR)‐positive, human epidermal growth factor receptor 2 (HER2)‐negative breast cancer. Methods In 2022, the Breast Cancer Expert Committee of the National Cancer Quality Control Center convened specialists in related fields to draft the “Expert Consensus on the Clinical Application of PI3K/AKT/mTOR Inhibitors in the Treatment of Advanced Breast Cancer.” This consensus raised awareness of these inhibitors among oncologists in China and improved the precision of clinical decision‐making. In recent years, growing evidence has emphasized the importance of targeting the PAM pathway, reflected in the approval of several innovative agents. This consensus is an updated 2025 edition that retains the foundational structure of the 2022 edition while incorporating notable updates. Results Updates to the consensus include the introduction of newly approved PAM pathway inhibitors, updated data from recent clinical trials, and expanded therapeutic applications. The revised guidance also offers updated recommendations for genetic testing to detect alterations in relevant pathways. The section on managing drug‐related adverse events has been significantly expanded, providing detailed insights into different types of adverse events and their management. These updates aim to enhance the clinical application of PAM pathway inhibitors, promote precision medicine, and ultimately, improve survival outcomes for patients with breast cancer.